The origin of the first and third generation fermion massesin a technicolor scenario - Doff, A.; Natale, A. A. (Springer, 2004)
We argue that the masses of the first and third fermionic generations, which are respectively of the order of a few MeV up to a hundred GeV, originate from a dynamical symmetry breaking mechanism leading to masses of the order alphamu, where alpha is a small coupling constant, and mu, in the case of the first fermionic generation, is the scale of the dynamical quark mass (approximate to250 MeV). For the third fermion generation mu is the value of the dynamical techniquark mass (approximate to250 GeV). We discuss how this possibility can be implemented in a technicolor scenario, and how the mass of the intermediate generation is generated.